Vascular distribution of nanomaterials. (28th April 2014) - Stapleton, Phoebe A.; Nurkiewicz, Timothy R.
Abstract Once considered primarily occupational, novel nanotechnology innovations, and applications have led to widespread domestic use and intentional biomedical exposures. With these exciting advances, the breadth and depth of toxicological considerations must also be expanded. The vascular system interacts with every tissue in the body, striving to maintain homeostasis. Engineered nanomaterials (ENM) have been reported to distribute in many different tissues and organs. However, these observations have tended to use approaches requiring tissue homogenization and/or gross organ analyses. These techniques, while effective in establishing presence, preclude an exact determination of where ENM are deposited within a tissue. If nanotechnology is to achieve its full potential, it is necessary to identify this exact distribution and deposition of ENM throughout the cardiovascular system, with respect to vascular hemodynamics and in vivo ENM modifications taken into account. Distinct levels of the vasculature will first be described as individual compartments. Then the vasculature will be considered as a whole. These unique compartments and biophysical conditions will be discussed in terms of their propensity to favor ENM deposition. Understanding levels of the vasculature will also be discussed. Ultimately, future studies must verify the mechanisms speculated on and presented herein. Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.